Komunikasi Mitigasi Bencana Dalam Mengurangi Resiko Bencana Bagi Masyarakat Pasaman Barat Sumatera Barat - Fernanda, Dian; Harahap, Muhammad Said (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2024)
The implementation of mitigation certainly requires communication so that it can be accepted by the community. One of the areas where a disaster occurred was West Pasaman Regency, West Sumatra. The role of BPBD is needed in handling disasters and reducing disaster risks for the community. West Pasaman Regency BPBD must be able to invite the community to work together so that the risk of disaster can be avoided. The aim of this research is to provide an overview of disaster mitigation communication in reducing disaster risk for the people of West Pasaman, West Sumatra. The research method used is qualitative research with a descriptive approach. Data collection techniques are through observation, interviews and documentation. Data analysis techniques are data reduction, data presentation, and drawing conclusions. The research results show that the communication carried out by BPBD West Pasaman Regency uses direct and indirect communication (social media and print media). This step is able to reduce the risk of disasters, because with disaster mitigation communication, the community has knowledge, skills, and knows the steps that must be taken before a disaster occurs, during a disaster, and after a disaster occurs. Communities can reduce the risk of loss of property, protect themselves and their families to avoid disaster victims.